Single-nucleotide polymorphisms in the IL-4 and IL-13 promoter region in aggressive periodontitis - J. R. Gonzales (Blackwell Synergy, 2007)
Introduction: IL-4 and IL-13 polymorphisms have been shown to influence the susceptibility to systemic diseases. In this study, possible associations between the IL- 4 590 C ! T, IL-4 34 C ! T, IL-13 1112 C ! T and IL-13 1512 A ! C promoter polymorphisms were investigated in subjects with generalized aggressive periodontitis (AgP) compared with healthy individuals. Material and Methods: Fifty-eight patients with diagnosis of generalized AgP and 51 matched healthy controls participated in the study. Blood samples were collected and DNA isolated. Molecular analyses were performed by PCR-RFLP in a blind fashion. Genotype and allele frequencies among study groups were compared using Fisher’s exact test (a value: 0.05). Pearson’s w2 test was used for analysis of Hardy–Weinberg equilibrium. Results: The frequency of the IL-4 590 T/T and IL-4 34 T/T genotypes differed significantly between groups (p50.05, 0.02, respectively), although the allele frequencies were similar. There was a higher frequency of the IL-4 590 T/T and IL-4 34 T/T genotypes in patients with AgP compared with controls. The genotype and allele frequencies of the IL-13 polymorphisms did not differ between groups. Conclusions: This study demonstrated an association between the IL-4 590 T/T and IL-4 34 T/T genotypes and AgP. Further research is necessary to prove if there is an association of these polymorphisms with AgP, and if the polymorphisms have a functional effect.